Burundi : Enhanced Initiative for Heavily Indebted Poor Countries; Decision Point Document. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper explains Burundi's Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). Burundi's social indicators reflect the effects of poverty compounded by decades of violence. The government's Interim Poverty Reduction Strategy Paper (I-PRSP) is based on broad consultations, but limited in some provinces by security conditions. The debt sustainability analysis (DSA) shows that even after HIPC assistance, Burundi would remain above the HIPC threshold for a considerable period of time, leaving it vulnerable to prolonged risk of debt distress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet